Analisis Study Kelayakan dan Pola Bisnis Pengelolaan Obyek Wisata Di Bendungan Teritip - Mursalim, Zilfana (LPPM University 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe purpose of this study is to analyze economic growth in the dam area and its buffer zone and formulate a business pattern for managing public economic zones. The analytical method used in this study is a comparative descriptive method with data collection methods through field surveys that produce primary and secondary data. Whereas the analysis tool is by looking at the contribution to Regional Original Revenue (PAD), using investment criteria with the Net Present Value (NPV) Method, the Internal Rate of Return (IRR) Method, the Net Benefit Cost Ratio (Net BC) Method and Sensitivity and Business Patterns with using Business Model Canvas (BCM). The results of a feasibility study of investment in developing public zones in the Teritip Dam can drive and trigger the growth of other economic sectors with a very broad range, where a number of workers will be absorbed in tourism activities and contribute significantly to PAD through retribution. Real economic activities including creative industries around the Teritip Dam public zone can also develop which will improve the welfare of the community.Keywords: Public economy, feasibility study, canvas business model,